The Aphaereta Förster species of the Carpathian Basin (Central-Europe) (Hymenoptera, Braconidae: Alysiinae). - Papp, Jenö (Contributions to Entomology = Beiträge zur Entomologie, 1965)
During the exploration of the Hungarian synanthrop and synbovin flies — carried out by the Institute of Public Health — a lot of Braconid specimens were bred which belong to the genus Aphaereta Förster. On the base of the bred material and the collection of the Hungarian Natural History Museum it was necessary to elaborate the Aphaereta Förster species of the Carpathian Basin from the viewpoint of taxonomy and zoogeography. After this elaboration it is possible to investigate the detailed ecology of that species. As a result of the taxonomical work we now know 4 Aphaereta Förster species (Aphaereta brevis Tobias, Aphaereta difficilis Nixon, Aphaereta minuta Nees, and Aphaereta tenuicornis Nixon) in the Carpathian Basin, but this number will increase in the future investigation. The monography contains the characterization of the genus Aphaereta Förster, the key of the four species, a minute description of the species, and the enumeration of the localities of the species in the Carpathian Basin. Nomenclatural Acts confluens Ratzeburg, 1844 (Alysia), syn. n. of Aphaereta minuta (Nees, 1811)